Pengaruh Taste dan Product Variation Terhadap Keputusan Pembelian Kopi Kenangan Pada Mahasiswa Fakultas Sosial Sains Universitas Pembangunan Panca Budi - Amanda, Tiara Dwi; Lestari, Indawati (Universitas Medan Area, 2024)
This research was carried out to explore the impact of Taste, Product Variation on the Decision to Purchase Kenangan Coffee. This type of research is an associative quantitative approach. The population in this research is the total number of active students at the Social Science Faculty of Panca Budi Development University in 2019-2023, totaling 5,200 people. The sampling technique used was purposive sampling which set criteria for respondents aged more than 17 years, active students and familiar with the Memories Coffee product so that a sample of 99 respondents was obtained. Data collection uses a questionnaire. The data analysis method uses several tests such as classic assumption tests, hypothesis testing and data analysis techniques using regression analysis. The research findings show that the Taste variable has positive and crucial implications for Purchasing Decisions and the Product Variation variable has a beneficial impact and also has an important impact on Purchasing Decisions and collectively the Taste and Product Variation variables have a beneficial and positive impact on the Purchasing Decision of Memories Coffee among Faculty students Social Science, Panca Budi Development University.